Supramolecular Translation of Enzymatically Triggered Disassembly of Micelles into Tunable Fluorescent Responses. Issue 44 (14th September 2015) - Buzhor, Marina; Harnoy, Assaf J.; Tirosh, Einat; Barak, Ayana; Schwartz, Tal; Amir, Roey J.
Abstract The need for advanced fluorescent imaging and delivery platforms has motivated the development of smart probes that change their fluorescence in response to external stimuli. Here a new molecular design of fluorescently labeled PEG–dendron hybrids that self‐assemble into enzyme‐responsive micelles with tunable fluorescent responses is reported. In the assembled state, the fluorescence of the dyes is quenched or shifted due to intermolecular interactions. Upon enzymatic cleavage of the hydrophobic end‐groups, the labeled polymeric hybrids become hydrophilic, and the micelles disassemble. This supramolecular change is translated into a spectral response as the dye–dye interactions are eliminated and the intrinsic fluorescence is regained. We demonstrate the utilization of this molecular design to generate both Turn‐On and spectral shift responses by adjusting the type of the labeling dye. This approach enables transformation of non‐responsive labeling dyes into smart fluorescent probes.